Respiratory tract infection is the major cause of the ambulatory visits in children - Lue KoHuang; Ku MinSho; Liao PeiFen; Sun HaiLun (BMC, 2011)
Abstract Background As children represent the future, ensuring that they receive proper health care should be a primary concern of our societies. Epidemiological research underpins the importance of effective child health care strategies, and highlights the need for accurate data collection; such surveys are currently lacking in Taiwan. In our descriptive studies, we compared the differences of the ten most common diseases in the year 2000 and 2009 among Taiwanese children. Methods Data for a total of 174,651 and 142,200 visits under eighteen years old were collected from the National Health Insurance Research Database in year 2000 and 2009. A maximum of three outpatient diagnostic codes (the International Classification of Disease [ICD], ninth revision) could be listed for every visit. Data were categorized according to the principal diagnoses, age and different specialties of physicians. Results Respiratory tract infection was the most common disease (58.21% to 44.77%). Teeth (4.90% to 5.16%) and eye (2.52% to 3.15%) problems were the also in the list of top ten diseases. In year 2009, the rate of allergic rhinitis was 2.87% in 7-18 years old group. Pediatricians were the first option for consultation, followed by ear, nose and throat specialists and family physicians. However, for the school age children group, the role of pediatricians with regards to children's health care showed a decrease in its importance. Conclusions The amount of information relevant to child health care is rapidly expanding. The ten most common diseases of the present analysis may serve as baseline data for future evaluations of the changes of type of diseases among children.